Isolation and clinical sample typing of human leptospirosis cases in Argentina - Chiani, Yosena (2015)
Leptospira typing is carried out using isolated strains. Because of difficulties in obtaining them, direct identification of infective Leptospira in clinical samples is a high priority. Multilocus sequence typing (MLST) proved highly discriminatory for seven pathogenic species of Leptospira, allowing isolate characterization and robust assignment to species, in addition to phylogenetic evidence for the relatedness between species. In this study we characterized Leptospira strains circulating in Argentina, using typing methods applied to human clinical samples and isolates. Phylogenetic studies based on 16S ribosomal RNA gene sequences enabled typing of 8 isolates (6 Leptospira interrogans, one Leptospira wolffii and one Leptospira broomii) and 58 out of 85 (68.2%) clinical samples (55 L. interrogans, 2 Leptospira meyeri, and one Leptospira kirschneri). MLST results for the L. interrogans isolates indicated that five were probably Canicola serogroup (ST37) and one was probably Icterohaemorrhagiae serogroup (ST17). Eleven clinical samples (21.6%), provided MLST interpretable data: five were probably Pyrogenes serogroup (ST13), four Sejroe (ST20), one Autumnalis (ST22) and one Canicola (ST37). To the best of our knowledge this study is the first report of the use of an MLST typing scheme with seven loci to identify Leptospira directly from clinical samples in Argentina. The use of clinical samples presents the advantage of the possibility of knowing the infecting strain without resorting to isolates. This study also allowed, for the first time, the characterization of isolates of intermediate pathogenicity species (L. wolffii and L. broomii) from symptomatic patients.